Effect of n-6/n-3 PUFA ratio on body fat deposition, tissues fatty acid composition and key genes expression of liver lipid metabolism in silver foxes (Vulpes vulpes fulva) during the winter fur-growth period - Zhong, Wei; Luo, Guoliang; Luo, Jing; Guo, Li (Frontiers in Veterinary Science, 2022)
（Objective）The proportion of n-6 /n-3 PUFA plays an important role in regulating lipid metabolism. This study aimed to investigate the effects of dietary n-6/n-3PUFA ratios on body fat deposition, tissues fatty acid composition and genes expression of liver lipid metabolism of silver foxes during the winter fur growth period.（Methods）Forty-eight age-matched male silver foxes with similar body weights were randomly divided into four dietary groups for 47 days, which were fed n-6/n-3 PUFA ratio with 3, 18, 41 and 136 experimental diets, respectively.（Results）Dietary n-6/n-3 PUFA ratio did not significantly influence fat deposition parameters except for hepatic fat content. The variation trend of fatty acid composition of liver, intramuscular fat and subcutaneous fat in silver fox were directly related to dietary fatty acid content (P <0.05). With dietary n-6/n-3 PUFA ratio increasing, the expression of liver FASmRNA and PPARmRNA exhibited the trend of first decreasing and then increasing (P <0.05), whereas L-FABPmRNA expression showed gradual increasing trend (P <0.05).（Conclusion）In summary, silver foxes fed n-6/n-3 PUFA ratio 18:1 diet (supplementing with 9.38% corn oil and 4.62% soybean oil ) was more conducive to lipid decomposition, PUFA transport and utilization of tissues, thereby to meet it for supplying energy and withstanding the cold.